Fracturas expuestas, manejo y complicaciones en el Hospital General Isidro Ayora - Tapia Merchán, Michelle Anabel (2021)
Exposed fractures are very frequent in our environment, at the same time they are susceptible to multiple acute or chronic complications caused by their severity and poor management. In our country there is tiny updated literature about this topic, especially locally. The present research is an observational, descriptive, non-experimental study. Information was collected on a data form about patients who had exposed fractures at the Isidro Ayora General Hospital in Loja city during the period june 2018 to may 2019. The information was tabulated in Excel datasheet for subsequent analysis and development of charts. The most relevant data were; male (82.6%) with an average age of 30 years. Exposed fractures, stand out Gustilo-Anderson grade II (35.48%), overcoming Gustilo IIIA (27.42%). More than 70% of cases were attended in > 6 hours period, what caused complications (43.55%), mainly infectious cause (19.35%). This study results are similar to the literature investigated. Further studies on the subject are recommended to reinforce the results found. Keywords: Exposed fractures, Management, Complications.